Decision Making in National Olympic Federation Leaderships from the Personnel's' Point of View - Mahdi Said Atiaa; Zaydoon Jwad Mohammed (College of Physical Education and Sport Sciences, 2021)
The importance of the research lies in decision-making in administration especially in sports and Iraqi national federations. The problem of the research lies in hasty decisions that lead to confusion in work a matter that affect the development of work. The research aimed at building and standardizing a scale for national Olympic federations' decision-making from the person's point of view. The researcher used the descriptive method on (163) coaches of national Olympic federations for the season (2020 - 2021). Building subjects were (100) coach then (40) coaches of (2019 - 2020) were used subjects. Finally, the researchers recommended designing and standardizing a scale for national Olympic federation leadership decision-making from a personal point of view.